Abelmoschus moschatus extract reverses altered pain and neurohistology of a rat with developmental exposure of fluoride - Kurmeti Sudhakar, Mesram Nageshwar, Karnati Pratap Reddy (Journal of Applied Pharmaceutical Science, 2018)
Fluoride causes major human health complications and evidence suggests that exposure of fluoride during developmental periods adversely affect neurodevelopment, behavior, and maturity of the brain as these periods are critical for developing stages for CNS. The present study aimed to assess the mechanically induced pain sensitivity, cell morphology, circuitry in terms of neural connections and networks and maturation of neurons under fluoride-induced toxicity with concurrent treatment of protective effects of Abelmoschus moschatus seed extract from day 1 of pregnancy to post-natal day (PND) of a rat with age 30th day. Timed pregnant wistar rats (30) were segregated into six groups, viz. control, sodium fluoride (NaF) (20 ppm), NaF + A. moschatus aqueous extract (AMAE), NaF + A. moschatus ethanolic extract (AMEE), AMAE, and AMEE and treated for 51 days (21 gestational and 30 post-natal days). On postnatal days 1, 7, 14, 21 and 30, rats were assessed for oxidative stress markers (GSH and GSSG) and neurohistology of the brain. Increased threshold levels to the mechanical stimulus were observed in fluoride-treated rats. Brain stained with Congo red, Cresyl violet and Golgi cox for β-amyloid, Nissl substance and synaptic connections respectively showed cells become amyloidosis with decreased Nissl substance and decreased number of neuronal connections in NaF exposed rats. Reduced content of GSH and increased GSSG levels (P < 0.001) were also recorded in NaF treated rats. These alterations were associated with increased production of free radicals and the effect of fluoride on the brain is inversely proportional with age. These changes were ameliorated by supplementation with AMAE and AMEE with anti-oxidant properties, which reduce the production of free radicals from fluoride. Thus, the seed extract of A. moschatus had a protective effect over fluoride induced alteration in neural cell maturation, and the establishment of circuitry, mechanical pain sensitivity, and oxidative stress.
Keywords: Abelmoschus, Cresylviolet, Fluoride, &beta; -amyloid,Nissl substance,Neurodegeneration.